The Aerobic and Anaerobic Endurance Profile of Male Basketball Athletes at Paradice Basketball Academy Surau Gading in 2025 - Bastian Criven Pratama Sitompul; Ardo Yulpiko Putra; Muhammad Prawibowo (Universitas Cahaya Prima, 2026)
Basketball requires athletes to possess good physical conditioning, particularly aerobic and anaerobic endurance, to support high-intensity and repeated activities during a game. Therefore, assessing athletes’ physical condition is essential to evaluate their capabilities and to design appropriate training programs. This study aimed to determine the aerobic and anaerobic endurance profiles of male basketball athletes at Paradice Basketball Academy Surau Gading in 2025. This study employed a quantitative descriptive approach using a survey method through testing and measurement. The research subjects consisted of 10 athletes who completed all testing procedures. Anaerobic endurance was measured using the Running-based Anaerobic Sprint Test (RAST), while aerobic endurance was assessed using the Multistage Fitness Test (MFT) to estimate VO₂max values. The data were analyzed using descriptive statistics, including frequency, percentage, mean, minimum, maximum, and standard deviation. The results showed that 70% of the athletes were classified in the good category for anaerobic endurance (mean fatigue index = 7.42; SD = 3.94; min = 0.83; max = 12.33), while 50% of the athletes were categorized as moderate for aerobic endurance (mean VO₂max = 42.65; SD = 5.93; min = 33.2; max = 50.8). These findings indicate that although the athletes demonstrate relatively good anaerobic capacity, their aerobic endurance still needs improvement through a balanced training program.